A Comparative Study about the Impact of Primary Special Education on The Sustainable Development of Children with Intellectual and Development Disabilities studying in the Govt. Special Education Institutions of Punjab - Ahmad, Nadeem; Fazil, Hina (Annals of Human and Social Sciences, 2023)
Primary special education focuses on helping its students with intellectual and developmental disabilities (SWIDDs) to learn skills and values that enable them to earn sustainable livelihoods and become a useful citizen of the society. The basic purpose of this research article was to observe the perceptions of teachers about the impact of primary special education based on sub-scales improving the life quality, enhancing socialization skills, provision of learning & career opportunities, provision of educational facilities, parental involvement, improving teacher’s proficiency and employability. 200 teachers of SWIDDs were selected using probability sampling technique with .712 coefficient value of the self-designed instrument. The study concluded that there is a significant impact of primary special education on the sustainable development (r=.321, P=.000). It was recommended that special education teachers should highlight the required facilities for the sustainable development of SWIDDs. The department of special education should increase the number of schools at tehsil and town level to fulfill the educational needs of SWIDDs.